2017
DOI: 10.1088/1361-6528/aa564d
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state nanopore localization by controlled breakdown of selectively thinned membranes

Abstract: We demonstrate precise positioning of nanopores fabricated by controlled breakdown (CBD) on solid-state membranes by spatially varying the electric field strength with localized membrane thinning. We show 100 × 100-nm2 precision in standard SiNx membranes (30-100 nm thick) after selective thinning by as little as 25% with a helium ion beam. Control over nanopore position is achieved through the strong dependence of the electric field-driven CBD mechanism on membrane thickness. Confinement of pore formation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 65 publications
0
69
0
Order By: Relevance
“…and Carlsen et al . reported that the breakdown can be localized in a selectively thinned membrane 46 , 47 . The spatial control over nanopore formation, combined with the nanopore count and diameter control pave the way for this type of nanopore array fabrication to find applications in optical measurement setups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and Carlsen et al . reported that the breakdown can be localized in a selectively thinned membrane 46 , 47 . The spatial control over nanopore formation, combined with the nanopore count and diameter control pave the way for this type of nanopore array fabrication to find applications in optical measurement setups.…”
Section: Resultsmentioning
confidence: 99%
“…Although the electric field strength decreased in other regions of the membrane, the existing defects keep growing in number. This growth allows the multiple nanopore formation 46 , 47 . To control the multiple nanopore formation process by adjusting the applied electric field, we consider the fabrication process a breakdown and an enlargement process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanopore fabrication by dielectric breakdown has a great advantage in terms of fabrication cost; expensive equipment, such as that needed for EB lithography, TEM or HIM, is not required. However, this method is rather unsuitable for the stable fabrication of a single large nanopore due to the risk of generating multiple nanopores 33 , 34 , 36 , 37 when trying to widen a nanopore by additional voltage stresses. Therefore, most of the nanopores used in previous studies 29 31 , 40 46 fabricated by dielectric breakdown were less than approximately 5 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a universal predetermined cutoff current is impossible to implement. False positive (negative) nanopore formation will occur if the cutoff current is set too low (high) [27,28,40,41]. To solve this issue, MPVI [31] was proposed.…”
Section: Introductionmentioning
confidence: 99%